Biocontrol fungi induced stem-base rot disease resistance of Morinda officinalis How revealed by transcriptome analysis - Chen, Zien; Han, Panpan; Che, Xiaoying; Luo, Zhenhua; Chen, Zeyu; Chen, Jinfang; Shan, Tijiang; Ding, Ping (Frontiers in Microbiology, 2023)
Morinda officinalis How (MO) is a Rubiaceae plant, and its medicinal part is dried root, which is one of the "Four Southern Medicines" in China. At present, the plant MO breed seedlings mainly by cutting methods. Long-term asexual propagation makes pathogenic fungi accumulate in MO, leading to stem-base rot, which is caused by Fusarium oxysporum (Fon). In this study, we identified Trichoderma harzianum and Pestalotiopsis sp. can be used to control Fon in the production of MO. The results showed that both Trichoderma harzianum and Pestalotiopsis sp. could inhibit the growth of Fon. In addition, Trichoderma harzianum and Pestalotiopsis sp. could also enhance the basic immunity to Fon by increasing the activities of defensive enzymes such as POD and SOD, chlorophyll content, soluble sugar content, and oligosaccharide content of MO. The mechanism of biological control of stem-base rot of MO was discussed by transcriptome technology. MO was treated with two treatments, root irrigation with biocontrol fungi or inoculation with Fon after root irrigation with biocontrol fungi. Transcriptome sequencing revealed that nearly 11,188 differentially expressed genes (DEGs) were involved in the process of inducing MO systemic resistance to Fon by biocontrol fungi. Meanwhile, Gene Ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment, as well as transcription factor (TFs) prediction showed that there were significant differences in the expression levels of MO roots under different treatments. Also, the genes of the "MAPK signaling pathway" and "plant hormone signaling pathway" were analyzed, in which the ERFs gene of the ethylene signal transduction pathway participated in the metabolism of glycosyl compounds. It is speculated that the ethylene signal may participate in the immune response of the sugar signal to the infection of Fon. After qRT-PCR verification of 10 DEGs related to the ethylene signal transduction pathway, the expression trend is consistent with the results of transcriptome sequencing, which proves the reliability of transcriptome sequencing. In conclusion, this study preliminarily identified the molecular mechanism of the biological control of MO stem-base rot and provided a scientific basis for further research on the prevention and control mechanism of MO stembase rot.